Achieving the 2°C goal: the potential of India's building sector. Issue 1 (2nd January 2019) - Graham, Peter; Rawal, Rajan
ABSTRACT: India's growth of energy demand in the building stock, and efforts to curb it, are placed into an international context by adapting the reporting criteria developed for the Global Alliance on Building & Construction's (GABC) Global Status Report (2017) on buildings and construction. A survey of state and non-state actor climate commitments submitted to the United Nations Framework Convention on Climate Change's (UNFCCC) Non State Actors Zone for Climate Action (NAZCA) database and recent research on the status of building energy codes and standards globally are also presented. To contribute to a 2°C pathway, India must achieve a 50% reduction in building energy demand and related greenhouse gas (GHG) emissions by 2050. India is taking steps toward this goal through initiatives such as recent upgrades to the Energy Conservation Building Code (ECBC), encouraging green building rating and energy certification, and stimulating markets for low-carbon/high-efficiency technologies. However, despite improvements in building energy intensity, neither the global or the Indian building sectors are currently decarbonizing. The adoption of consistent national energy and GHG emission reduction goals could further align national, subnational and private-sector climate action commitments to facilitate a transition to a low-carbon emissions pathway and contribute to limiting global warming to well below 2°C.